Seasonal Dynamics and Diversity Analysis of Phytoplankton in Lakshmipuram Lake, Anakapalli District, Andhra Pradesh, India - Pratap, Gudabandi Vijaya; Rao, Tulasi Bhushan; Lakshman, Palaka; Keerthana, Bora (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Phytoplankton play a vital role in aquatic ecosystems as primary producers, and their diversity serves as a key indicator of water quality and ecological health. The present study investigates the phytoplankton diversity of Lakshmipuram Lake, located in Anakapalli district of Andhra Pradesh, over a one-year period from January 2024 to December 2024. Phytoplankton samples were collected from three different sites across three seasons—pre-monsoon (March–May), monsoon (June–September), and post- monsoon (October–December)—using standard methods outlined in Standard Methods for the Examination of Water and Wastewater. Collections were conducted in the morning between 7:00 am and 9:00 am using a 5 μm mesh phytoplankton net and preserved in 3% formaldehyde solution. The samples were examined under an optical microscope, and species identification was carried out using standard identification keys and reference guides. A total of 29 genera belonging to three major classes—Chlorophyceae (15 genera), Cyanophyceae (8 genera), and Bacillariophyceae (6 genera)—were identified. Among these, Chlorophyceae was the dominant class, contributing 51.7% of the total genera; Cyanophyceae (27.6%) and Bacillariophyceae (20.7%). Seasonal variations revealed that phytoplankton abundance was highest during the pre-monsoon due to increased levels of salinity, temperature, pH, alkalinity, TDS, hardness, chlorides, nitrates, phosphorus and lowest during the monsoon season due to high rainfall, reduced salinity, pH, temperature. Diversity indices indicated moderate diversity and evenness across the lake. The Shannon-Wiener diversity index ranged from 1.0363 to 1.0483 with an average of 1.043, while the Evenness index (Pielou’s J′) ranged from 0.3077 to 0.3113 with an average of 0.310, showing a moderately stable and evenly distributed phytoplankton community. The study concludes that Lakshmipuram Lake supports a diverse and moderately productive phytoplankton community, which varies significantly with seasonal changes. The findings provide valuable baseline data for future ecological assessments and contribute to the effective conservation and management of this freshwater ecosystem.